History of the Graeco-Latin fable - Adrados, Francisco Rodríguez, 1922- (Mnemosyne, Supplements, 1999)
Spanning from Sumer to the present day few literary genres show greater continuity throughout their history than the fable. Historical evidence reaching as far back as Antiquity, supports the study of more than 500 works considered to be fables. This translation of the original Spanish, standard work on the fable, traces the history of the Graeco-Latin fable, investigates its origins, reconstructs lost collections from the Hellenistic Age, and establishes relationships between the fablist of the Imperial Age and the study of Medieval, Greek and Latin fables. Supplements at the end of each chapter have been added, giving information on a new bibliography and some new data, together with references to subsequent studies.